Purification Of Novel Enzymes From Newly Isolated Indigenous Soil Bacterial - Liu, Meng; Roziah, Hj Kambol (2009)

(untitled)
The culturability of bacteria in the bulk soil of an Malaysia palm oil plantation was investigated by using nutrient agar at of its normal concentration (dilute nutrient agar) as the growth medium. Some newly enzymes were purified from these microorganisms. We collected soil samples and isolated microorganism from it and screened in incubator. so far, six isolates obtained from plate and completed a series of culture conditions including temperature ,ph and so on. But identification by comparative analysis of partial 16S rRNA gene sequences and their biochemical test by API kit are still in the process. Two crude enzymes purified from microorganisms were assayed by using crude palm oil as substrate, the crude enzymes have activity in transestefication reaction as biocatalyst.